(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
The confluence of art, politics, and aesthetics has a troubled and troubling history, and the article reflects on that by examining the aesthetics of Uli Edel’s filmDer Baader Meinhof Komplex in terms of its use of iconic historical and—in terms of film history—stereotypical images. The absence of conventional narrative structures in the film opens it up to methods of understanding and critique that use image and montage as a means of analysis, rather than examining a cogent (because absent) narrative. By cataloguing the use of different genre conventions and iconic film images and tropes, the article points toward the development of a “terror(ism)” genre.